Adjustment Problems Among College Students (Voice of Teacher, 2021)
This study investigates the adjustment problems of college students. The main objectives of the study were to assess the level of adjustment problem of college students and find out the relationship between adjustment problems and stress level. The sample consists of 300-college students 150 male and 150 female from Tribhuvan University Constituent and affiliated colleges in the Kathmandu Valley. The adjustment inventory for college students (AICS) by Dr A. K. P. Sinha and Dr R. P. Singh, Stress Measurement Scale developed by the British Heart Foundation (Stress and your Heart) were used. The methodology includes a descriptive survey design with a purposive sampling technique. The univariate statistics and Pearson’s Product-moment correlation method was used to analyze the data. Analysis of the result revealed that college students have an average level of adjustment and Among all adjustment area emotional adjustment was more pronounced than others. It was also found that male students were better adjusted than female students. The value of the correlation between stress and adjustment level were found positive(r>0) for both male and female students.